The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40249-017-0356-5
|View full text |Cite
|
Sign up to set email alerts
|

Plague risk in vulnerable community: assessment of Xenopsylla cheopis susceptibility to insecticides in Malagasy prisons

Abstract: BackgroundPrisons in Madagascar are at high risk of plague outbreak. Occurrence of plague epidemic in prisons can cause significant episode of urban plague through the movement of potentially infected humans, rodents and fleas. Rodent and flea controls are essential in plague prevention, by reducing human contact with plague reservoirs and vectors. Insecticide treatment is the key step available for the control of rat fleas which transmit the disease from infected rodents to human. The implementation of an ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…cheopis on rats [13]. In addition, insecticide susceptibility tests showed great susceptibility to fenitrothion and is consistent with previous studies [31,36]. Our study demonstrated that this conventional treatment remained effective during the first week after treatment, adding supplementary protection to the community.…”
Section: Discussionsupporting
confidence: 92%
“…cheopis on rats [13]. In addition, insecticide susceptibility tests showed great susceptibility to fenitrothion and is consistent with previous studies [31,36]. Our study demonstrated that this conventional treatment remained effective during the first week after treatment, adding supplementary protection to the community.…”
Section: Discussionsupporting
confidence: 92%
“…The use of chemicals to eliminate fleas or rodents requires the surveillance of physiological resistance mechanisms in flea/rodent populations and the identification of biochemical or genetic markers of resistance as well as the characterization of mechanisms involved and their environmental and genetic determinants. Studies on X. cheopis insecticide resistance have already been carried out in different situations [41,42]. However, information on other flea species is most often missing.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Studies on X . cheopis insecticide resistance have already been carried out in different situations [ 41 , 42 ]. However, information on other flea species is most often missing.…”
Section: Which Hosts and Vectors Should Be Targeted For Human Plague mentioning
confidence: 99%
“…Xenopsylla cheopis pode transmitir as doenças como: tifo murino ou tifo endêmico causadas pelas bactérias da Família Rickettsiaceae, Rickettsia typhi e R. mooseri, parasitos intracelulares obrigatórios (SAAVEDRA; DIAS, 2011;MIARINJARA et al, 2017). Também podem transmitir Revista um bacilo Gram-negativo, denominado Yersinia pestis, causadora da peste bubônica, de duas formas: mecânica e biologicamente.…”
Section: Introductionunclassified